UTILIZATION OF TRICHO-COMPOST AND LOCAL MICROORGANISMS TO SUPPORT ORGANIC FARMING FOR THE ORA ET LABORA FARMER GROUP IN KUPANG CITY - Mayavira Veronica Hahuly; Agnes Virginia Simamora; Petronela Syahyanti Nenotek; Agustina Etin Nahas; Shirly Seahan Oematan; Effy Roefaida; Ewaldus Tan; Jericho Albert Balol; Theodosius Lau Base; Fadlan Pramatana (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The “Ora et Labora” Farmer Group in Naioni Village, Kupang City, has developed horticultural and livestock farming on a three-hectare area cultivating long beans, tomatoes, and chilli peppers using a drip irrigation system. Despite these advancements, farmers remain dependent on chemical fertilizers and pesticides, which over time damage soil structure, reduce fertility, and disrupt the balance of soil microorganisms. To address this issue, an organic farming system was introduced as an environmentally friendly alternative using tricho-compost based on Trichoderma spp. and Local Microorganisms (MOL). Tricho-compost improves nutrient availability and suppresses soil-borne pathogens, while MOL acts as a natural starter for organic matter fermentation and a potential biocontrol agent. This Community Service Program (PKM) aimed to enhance farmers’ understanding and skills in producing and applying tricho-compost and MOL. The results demonstrated improved knowledge, technical ability, and motivation among farmers to independently implement organic farming, thereby promoting sustainable and environmentally friendly cultivation systems.